Evaluating the Salary Mismatch Among Secondary School Teachears in Rubanda District. - Atukwase, Brian (Kabale University, 2024)
This study examined the issue of salary mismatches among secondary school teachers, focusing on the discrepancies between their qualifications, experience, and the compensation they receive. Salary mismatch, defined as the gap between a teacher's salary and their professional qualifications or job responsibilities, has become a significant concern in the education sector. The study aimed to achieve three objectives: to analyze the current salary structures for secondary school teachers, to evaluate the impact of salary mismatches on teacher motivation, job satisfaction, and retention, and to propose strategies to mitigate the negative effects of salary mismatches in Rubanda District. The research sought to identify the extent of salary mismatch, its underlying causes, and its implications for the education system. A mixed-methods approach was used, combining quantitative data analysis and qualitative interviews. Data were collected from a sample of secondary school teachers from different regions, including salary records, teacher qualifications, and years of experience to assess the prevalence and degree of salary mismatches. Qualitative data were gathered through interviews with teachers, administrators, and policymakers to understand their views on salary fairness, the causes of salary discrepancies, and the impact on teacher performance and morale. The study found significant salary mismatches, with many teachers earning less than what would be expected based on their qualifications and experience. Contributing factors included inconsistent pay scales, budget constraints, and regional disparities in funding and resources. The study also emphasized the negative effects of salary mismatches on teacher morale and retention, suggesting that addressing these issues is essential for improving educational outcomes. Policy recommendations include standardizing pay scales, increasing education funding, and implementing targeted interventions to support underpaid teachers. Addressing salary mismatches could improve teacher satisfaction and effectiveness, leading to better student learning and achievement.